2016
DOI: 10.1038/ncomms13781
|View full text |Cite
|
Sign up to set email alerts
|

A cell-autonomous tumour suppressor role of RAF1 in hepatocarcinogenesis

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer deaths, but its molecular heterogeneity hampers the design of targeted therapies. Currently, the only therapeutic option for advanced HCC is Sorafenib, an inhibitor whose targets include RAF. Unexpectedly, RAF1 expression is reduced in human HCC samples. Modelling RAF1 downregulation by RNAi increases the proliferation of human HCC lines in xenografts and in culture; furthermore, RAF1 ablation promotes chemical hepatocarcinogenesis and the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…However, there exists only one striking study which unexpectedly discovered a RAF1 expression reduction in human HCC samples. In this study, RAF1 downregulation increased the proliferation of HCC in xenografts and in culture [21]. Our conclusion seems to point that highly expressed RAF1 is associated with sorafenib resistance.…”
Section: Discussionsupporting
confidence: 64%
“…However, there exists only one striking study which unexpectedly discovered a RAF1 expression reduction in human HCC samples. In this study, RAF1 downregulation increased the proliferation of HCC in xenografts and in culture [21]. Our conclusion seems to point that highly expressed RAF1 is associated with sorafenib resistance.…”
Section: Discussionsupporting
confidence: 64%
“…Our results showed that miR-340-3p, miR-669d, miR-374 and miR-338-5p could directly target circadian genes (miR-340-3p targeting Clock , Per1 , Cry2 ; miR-669d targeting Per2 ; miR-374 targeting Per3 ; miR-338-5p targeting Nr1d1 ), further supporting this idea. The other main pathway was pathway in cancer, and the genes in this pathway can impact tumor cell proliferation (PPARG, RAF1), regulate hepatic glucose and lipid metabolism (FOXO1), and decrease the viability and invasiveness of HCC cells (RALA) (Ezzeldin et al, 2014; O-Sullivan et al, 2015; Jeric et al, 2016; Li et al, 2017; Savic et al, 2016). This suggests that at the molecular level, CLOCK-regulated miRNAs may be involved in cancer initiation or progression by directly controlling cell proliferation, cell invasion, or metabolism-related genes in the mouse liver.…”
Section: Discussionmentioning
confidence: 99%
“…while ECs together with keratinocytes, mouse embryonic fibroblasts or macrophages were unaffected by deletion of RAF1 [15]. Whether BRAF ablation in hepatocellular carcinoma has similar effects is currently unknown and warrants further investigation.…”
Section: Perspectivesmentioning
confidence: 98%
“…observed in lung ECs. Further evidence of tissue specificity for RAF1 comes from the liver, where RAF1 ablation in hepatocellular carcinoma promoted proliferation and carcinogenesis, while ECs together with keratinocytes, mouse embryonic fibroblasts or macrophages were unaffected by deletion of RAF1 . Whether BRAF ablation in hepatocellular carcinoma has similar effects is currently unknown and warrants further investigation.…”
Section: Perspectivesmentioning
confidence: 99%